Arch of Triumph from Court of Flowers on Treasure Island (H.S. Crocker Co., Inc.)
From the Court of Flowers, with its fountain of the Girl and the Rainbow, one looks through the Arch of Triumph into the Court of Reflections, as San Francisco's beautiful World's Fair.